Contribution of risk factors to socioeconomic variation in blood pressure : the Tromsø study - Asfaw, Sintayehu (Universitetet i Tromsø, 2012)
Abstract Objectives: Examine the degree to which BMI, heart rate, physical activity, alcohol intake, smoking and social participation may account for the association between socioeconomic status (SES) and systolic blood pressure (SBP), with main focus on measured SBP continuous variable. Design: Cross-sectional study with data from the Tromsø study 6. Setting: Tromsø Participant: The sample included 6095 women and 5419 men, aged 30 – 87 at screening. Results: High SBP was more prevalent for women and men with the lowest education compared with women and men with the highest education. After adjustment for heart rate the differences in SBP between the highest and the lowest educated groups reduced from 5.86 mmHg (95% confidence interval 4.32 to 7.40) to 5.61 mmHg (4.07 to 7.16) for women, and for men from 2.48 mmHg (0.92 to 4.04) to 1.96 mmHg (0.39 to 3.52) with further adjustment for BMI, physical activity, alcohol intake, smoking and social participation the variation in SBP decreased to 5.39 mmHg (3.78 to 6.99) for women and to 1.60 mmHg (– 0.04 to 3.25) for men. Conclusions: High SBP is more predominant among the lowest educated compared with the highest educated women and men. When all documented risk factors were adjusted simultaneously in the models, the differences in SBP turned into nonsignificance in men and 8% of the variation in SBP was explained in women according to levels of education.